Metal‐Free Oxidative Cyclization of o‐Acylphenols for the Construction of 2‐Aminobenzofuran‐3(2H)‐ones. Issue 15 (3rd April 2014) - Yu, Hui; Huang, Weihua; Zhang, Fengling
Abstract: An efficient metal‐free approach to the synthesis of 2‐aminobenzofuran‐3(2 H )‐ones has been developed. Using TBHP as an oxidant and I2 (or TBAI) as catalyst, 2‐acylphenols were treated with secondary amines to provide 2‐aminobenzofuran‐3(2 H )‐one derivatives in moderate to good yields. A possible reaction pathway for the formation of 2‐dimorpholinobenzofuran‐3(2 H )‐one is also discussed herein. Abstract : Oxidative coupling of 2‐acylphenols with secondary amines for the preparation of 2‐aminobenzofuran‐3(2 H )‐ones is reported. Using TBHP as oxidant and I2 (or TBAI) as catalyst, various 2‐aminobenzofuran‐3(2 H )‐one derivatives were synthesized in moderate to good yields.